1988
DOI: 10.1161/01.atv.8.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Deferred effects of preweaning diet on atherosclerosis in adolescent baboons.

Abstract: We examined the effects of breast and formula feeding during infancy on the serum llpoprotelns and on atherosclerosis in young adult baboons. Baboons were breastfed (n = 13) or formula-fed (n = 32) until weaning at 16 weeks of age and thereafter they were fed a diet containing 1.7 mg cholesterol/kcal and 40% of calories as lard until 5 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
6

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 30 publications
1
29
0
6
Order By: Relevance
“…He showed that rats raised in small litters, and therefore overfed early in postnatal life, are programmed for greater body size as adults. Subsequently, rats overfed in the brief suckling period have been shown to have higher plasma insulin and cholesterol concentrations (Hahn, 1984), while early nutrition in baboons has been found to have a major impact on later obesity (Lewis et al 1986) and atherosclerosis (Lewis et al 1988). The concept that factors early in life affect long-term health has been confirmed extensively in man.…”
Section: Historical Overviewmentioning
confidence: 99%
“…He showed that rats raised in small litters, and therefore overfed early in postnatal life, are programmed for greater body size as adults. Subsequently, rats overfed in the brief suckling period have been shown to have higher plasma insulin and cholesterol concentrations (Hahn, 1984), while early nutrition in baboons has been found to have a major impact on later obesity (Lewis et al 1986) and atherosclerosis (Lewis et al 1988). The concept that factors early in life affect long-term health has been confirmed extensively in man.…”
Section: Historical Overviewmentioning
confidence: 99%
“…Toutefois, la cholestérolémie était sensiblement plus élevée chez les femelles que chez les mâles. Complétant cette première étude, les auteurs ont ensuite examiné l'impact sur l'athérogénèse du babouin adolescent du lait maternel à 30 mg/dl vs. formule à 1 mg/dl suivi d'un régime athérogène à 1,7 mg/kcal (Lewis et al, 1988). Au sevrage, indistinctement du sexe, le rapport LDL+VLDL/HDLcholestérol était supérieur pour les babouins « formule », puis ce rapport s'inversait rapidement et restait constamment plus élevé pour les singes initialement allaités, y compris pendant l'enfance, ce qui contredit les résultats de l'expérience précé-dente (Mott et al, 1982).…”
Section: Les éTudes Chez L'animal Sur Le Rôle D'une Exposition Précocunclassified
“…Au sevrage, indistinctement du sexe, le rapport LDL+VLDL/HDLcholestérol était supérieur pour les babouins « formule », puis ce rapport s'inversait rapidement et restait constamment plus élevé pour les singes initialement allaités, y compris pendant l'enfance, ce qui contredit les résultats de l'expérience précé-dente (Mott et al, 1982). À 5,4 ans, le % d'athérosclérose était même supérieur pour les babouins allaités comparativement à ceux ayant reçu la formule (Lewis et al, 1988). La dernière étude finissant cette série reprenait un protocole semblable, comparant des singes allaités (22 mg/dl cholestérol) vs. formules à 2, 30, 60 mg/dl de cholestérol (Mott et al, 1990) des deux sexes, suivi d'un régime post-sevrage athérogène à 1 mg/kcal cholestérol mais administré jusqu'à l'âge adulte (7−8 ans).…”
Section: Les éTudes Chez L'animal Sur Le Rôle D'une Exposition Précocunclassified
See 1 more Smart Citation
“…For example, it was found that rats raised in small litters, and therefore overfed early in postnatal life, develop greater body size as adults (McCance, 1962). Subsequently, Hahn (1984) has shown that rats overfed in the brief suckling period have higher plasma insulin and cholesterol concentrations, while Lewis and Mott (Lewis et al 1986(Lewis et al , 1988 have shown that early nutrition in baboons has a major impact on later obesity (Lewis et al 1988) and atherosclerosis (Lewis et al 1986). There is now overwhelming evidence that early nutrition in a variety of animal species, including primates, can influence later CVD, including all components of the metabolic syndrome, learning and behaviour, intermediary metabolism, gut function, bone health, immunity and longevity (Smart, 1986;Dobbing & Sands, 1971;Desai et al 1995;Hales et al 1996;Symonds & Gardner, 2006).…”
Section: Earnest: Early Nutrition Programming Project: European Unionmentioning
confidence: 99%